Effect of substrate properties on isothermal fatigue of aerosol jet printed nano-Ag traces on flex. Issue 16 (28th August 2019) - Muralidharan, Roshan; Raj, Arun; Sivasubramony, Rajesh Sharma; Yadav, Manu; Alhendi, Mohammed; Nilsson, Matthew; Greene, Christopher; Poliks, Mark D.; Borgesen, Peter
Abstract: Abstract : Sintered nanoparticle structures are macroscopically brittle but quite robust if deposited on a flexible substrate. The effects of a polymer substrate on the stretchability of both brittle and ductile coatings and traces are well established. Systematic effects of substrate properties on the fatigue resistance of aerosol printed nano-Ag are slightly more complex. The present work is focused on the early stages of fatigue, where the resistance increases significantly but cracks are not yet visible. Overall, the fatigue behavior is seen to vary with the combination of substrate modulus and viscoelastic deformation properties. Comparing two common polyimides, the rate of damage was seen to increase faster with increasing amplitude on the less compliant one. Consistently with this increasing the minimum strain in the cycle led to a significantly stronger reduction in damage rates. However, the damage rate remained lower on the less compliant substrate at all amplitudes and strain ranges of practical concern.